Radiopacity of intracerebral hemorrhage correlates with perihemorrhagic edema - Wagner, Irina; Volbers, Bastian; Hilz, Max-Josef; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background: Experimental evidence indicates that iron plays a key role in edema formation after intracerebral hemorrhage (ICH). We investigated the relationship between ICH radiopacity on CT as a marker of hematoma iron content and perihemorrhagic edema (PHE) after ICH. Methods: We retrospectively investigated patients with spontaneous lobar and ganglionic supratentorial ICH who received follow-up CT scans during the first 7days after symptom onset (d1, d2-4, d5-7). Measurements of ICH and edema volumes were taken using a semiautomatic threshold-based volumetric algorithm. Radiopacity of the blood clot was determined using the mean Hounsfield unit (HU) count of the ICH. Results: A total of 117 patients aged 71.92±11.55years with spontaneous ICH (34.63±32.44ml) were included in the analysis. Mean ICH radiopacity was 59.7±3.4HU. We found significantly larger relative PHE at d2-4 (1.7±0.9 vs. 1.3±0.8; P=0.032) and d5-7 (2.0±1.3 vs. 1.3±0.9; P=0.007) and larger peak relative PHE (2.3±1.6 vs. 1.6±1.1; P=0.006) in patients with ICH radiopacity >60HU (n=59), as compared to patients with ICH radiopacity <60HU (n=58). Conclusions: Higher ICH radiopacity, reflecting higher in vivo hematoma iron content, is associated with more PHE after ICH. © 2011 The Author(s). European Journal of Neurology © 2011 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Intracerebral hemorrhage; Perihemorrhagic edema; Radiopacity